2012
DOI: 10.1096/fj.11-180992
|View full text |Cite
|
Sign up to set email alerts
|

Dynein light chain 8a of Toxoplasma gondii , a unique conoid‐localized β‐strand‐swapped homodimer, is required for an efficient parasite growth

Abstract: Dynein light chain 8 (DLC8) is a ubiquitous eukaryotic protein regulating diverse cellular functions. We show that the obligate intracellular parasite Toxoplasma gondii harbors 4 DLC8 proteins (TgDLC8a-d), of which only TgDLC8a clusters in the mainstream LC8 class. TgDLC8b-d proteins form a divergent and alveolate-specific clade. TgDLC8b-d proteins are largely cytosolic, whereas TgDLC8a resides in the conoid at the apical end of T. gondii. The apical location of TgDLC8a is also not shared by its nearly identic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
(55 reference statements)
0
16
0
Order By: Relevance
“…In addition to this improved understanding of LC8, interest in this molecule has grown as LC8 has been shown to have unique and important roles in an increasing number of human pathogens. These include viruses, such as HIV (26), Ebola (27), and rabies (28), and the protistan parasite Toxoplasma gondii (29).Trypanosoma brucei, a member of the early-diverging phylogenetic order Kinetoplastida, is a vector-borne parasite that causes lethal disease in both humans and livestock (30). In T. brucei, LC8 was identified in mass spectrometry analysis of the flagellum (31) and, surprisingly, as a subunit of the class I transcription factor A (CITFA) (32, 33).…”
mentioning
confidence: 99%
“…In addition to this improved understanding of LC8, interest in this molecule has grown as LC8 has been shown to have unique and important roles in an increasing number of human pathogens. These include viruses, such as HIV (26), Ebola (27), and rabies (28), and the protistan parasite Toxoplasma gondii (29).Trypanosoma brucei, a member of the early-diverging phylogenetic order Kinetoplastida, is a vector-borne parasite that causes lethal disease in both humans and livestock (30). In T. brucei, LC8 was identified in mass spectrometry analysis of the flagellum (31) and, surprisingly, as a subunit of the class I transcription factor A (CITFA) (32, 33).…”
mentioning
confidence: 99%
“…Previous studies have indicated that the homodimeric DLCs in S. mansoni [26] and F. hepatica [27] were composed of two asymmetric monomers through β-sheet interactions. The homodimer of CsTegu20.6 was constructed using GalaxyGemini [44] with only the C chain of DLC1 (PDB ID: 4DS1_C), although the fifth β-strand (indicated with a dotted circles) as a monomeric counterpart was missed in the predicted structure [45] (Figure 5C). This result suggests that CsTegu20.6 can dimerize, confirming that this feature is conserved between the DLCs.…”
Section: Resultsmentioning
confidence: 99%
“…The genome also contains annotated genes for several types of intermediate and light chains, including light chain type 1, Tctex-1, Roadblock/LC7, the axonemal assembly factor, axonemal light chain, and axonemal intermediate chain (69). Although overexpressed dynein light chain 1 (DLC1) fused to green fluorescent protein (GFP) localizes to the spindle poles, centrioles, the basal end, and the conoid region of tachyzoites (95), a subsequent study of a shortened version of the same protein (minus 49 aminoterminal residues, termed T. gondii DLC8a [TgDLC8a]) localizes it only to the apical region of tachyzoites (96). The latter study used a small epitope tag that was introduced as an in-frame fusion at the carboxy terminus of the endogenous locus.…”
Section: Microtubule-associated Proteinsmentioning
confidence: 99%
“…The complement of MAPs localizing to spindle microtubules remains largely uncharacterized, though several proteins have been identified on centrioles located at the spindle poles. Since DLC1/TgDLC8a localizes to the spindle only as an overexpressed GFP fusion protein (95,96), the plus-end binding protein EB1 (J. de Leon and N. Morrissette, unpublished observations) is the sole marker of mitotic microtubules. It is quite likely that dyneins and kinesins are spindle components, in addition to other, yet-to-be-characterized MAPs.…”
Section: Microtubule-associated Proteinsmentioning
confidence: 99%
See 1 more Smart Citation